2021
DOI: 10.1136/rmdopen-2021-001707
|View full text |Cite
|
Sign up to set email alerts
|

Use and detailed metric properties of patient-reported outcome measures for rheumatoid arthritis: a systematic review covering two decades

Abstract: IntroductionThe importance of patient-reported outcome measures (PROMs) for rheumatoid arthritis (RA) clinical studies has been recognised for many years. The current study aims to describe the RA PROMs used over the past 20 years, and their performance metrics, to underpin appropriate tool selection.MethodsThe study included a systematic search for PROMs that have been in use over the period 2000–2019, with detailed documentation of their psychometric properties, and a user-friendly presentation of the extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…measures of disease activity, functional status, mental health and QoL) for guiding the treat-to-target approach used to manage rheumatic diseases. 64 The COVID-19 pandemic and abrupt shift to virtual medical care have dramatically accelerated the implementation of PROs in rheumatology in developed countries as an important means of patient evaluation, ensuring adequate control of disease activity and response to antirheumatic treatments in the era of telemedicine. 65 A number of recent studies have shown that PROs, including disease-specific questionnaires for several rheumatic conditions [e.g.…”
Section: Patient-reported Outcome Data and Self-assessmentmentioning
confidence: 99%
“…measures of disease activity, functional status, mental health and QoL) for guiding the treat-to-target approach used to manage rheumatic diseases. 64 The COVID-19 pandemic and abrupt shift to virtual medical care have dramatically accelerated the implementation of PROs in rheumatology in developed countries as an important means of patient evaluation, ensuring adequate control of disease activity and response to antirheumatic treatments in the era of telemedicine. 65 A number of recent studies have shown that PROs, including disease-specific questionnaires for several rheumatic conditions [e.g.…”
Section: Patient-reported Outcome Data and Self-assessmentmentioning
confidence: 99%
“…Patientenberichtete Outcomes sind inzwischen ein fester Bestandteil klinischer Studien [ 16 ]. Auch im RABBIT-Register fragen wir die Patient:innen nach ihrem körperlichen (Wohl‑)Befinden, insbesondere zum derzeitigen Gesundheitszustand, zu Erschöpfung und Müdigkeit, Schmerzen und Schlafstörungen.…”
Section: Patient:innen Im Fokusunclassified
“…There are several generic and disease specific instruments used in measuring functional status among RA patients, such as the Barthel index for activities of daily living, the Groningen activity restriction scale (GARTH), the World Health Organization Disability Schedule-II (WHODAS-II), the Health Assessment Questionnaire Disability Index (HAQ-DI) Health Assessment Questionnaire II (HAQ-II), the shortened arthritis impact measurement scales (AIMS), the Multidimensional Health Assessment Questionnaire (MDHAQ-10-ADL), MDHAQ-14-ADL, and the Sickness Impact Profile (SIP-RA) to name few [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Some of these tools are inconsistently assessed for their psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these tools are inconsistently assessed for their psychometric properties. The majority were assessed for reliability, some were assessed for their factor structure, test-retest reliability and responsiveness, and a few were assessed for item discrimination, difficulty, and sensitivity [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%